2013
DOI: 10.1016/j.jped.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemic Waist Phenotype: Association with Metabolic Abnormalities in Adolescents

Abstract: This study demonstrated that the HTW phenotype was associated with an atherogenic lipid profile, and this phenotype is suggested as a screening tool to identify adolescents with metabolic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
4
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 21 publications
3
35
4
6
Order By: Relevance
“…In the present study, we explored for the first time in an Arabic adolescent cohort the nontraditional risk factor non-HDL-C and its patterns and associations compared with routinely used lipid profile in the assessment of cardiometabolic risk. The present study's overall prevalence of 20.8%, according to AAP, when compared with other epidemiologic data is higher than most ethnic groups, Non-Hispanic whites and Germans (11.5 and 11.9%, respectively), 4,13 non-Hispanic blacks, and Chinese (7.7% and 4.1%, respectively), 10 and Brazilian adolescents (16.6%), 11 suggesting ethnic variations. This high prevalence becomes much lower (10.1%), however, and thus is similar to the mentioned studies when cutoffs obtained from the cohort were used.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In the present study, we explored for the first time in an Arabic adolescent cohort the nontraditional risk factor non-HDL-C and its patterns and associations compared with routinely used lipid profile in the assessment of cardiometabolic risk. The present study's overall prevalence of 20.8%, according to AAP, when compared with other epidemiologic data is higher than most ethnic groups, Non-Hispanic whites and Germans (11.5 and 11.9%, respectively), 4,13 non-Hispanic blacks, and Chinese (7.7% and 4.1%, respectively), 10 and Brazilian adolescents (16.6%), 11 suggesting ethnic variations. This high prevalence becomes much lower (10.1%), however, and thus is similar to the mentioned studies when cutoffs obtained from the cohort were used.…”
Section: Discussioncontrasting
confidence: 42%
“…10,11 In this cross-sectional study, we aim to investigate for the first time the prevalence of elevated non-HDL-C in the adolescent Arab population as well its influence over other lipid subcomponents in predicting elevated blood glucose using the definitions proposed by the American Academy of Pediatrics (AAP) in diagnosing dyslipidemia in children. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Ademais, a cintura hipertrigliceridêmica em crianças e adolescentes está associada com um perfil lipídico aterogênico que imprime chances, aproximadamente, 2,5 vezes maiores para o desenvolvimento de HDL-c baixo quando comparada a indivíduos eutróficos (20) . Ao se analisar a quantidade de fatores de risco por cada indivíduo, apenas 28% da amostra, ou seja,117 indivíduos, não tinham nenhum dos cinco fatores analisados (PAS, PAD elevadas; sedentarismo; hiperglicemia; hipertrigliceridemia; valores de baixos de HDL-c).…”
Section: Resultsunclassified
“…Esmaillzadeh et al [7] showed that adolescents with the Hypertriglyceride Waist (HW) phenotype had significantly higher prevalence of all metabolic risk factors except elevated fasting glucose than those without the HW phenotype. Also, Brazilian investigators [22] showed that HW phenotype in adolescents was positively associated with high non HDL cholesterol and low HDL-C levels. Thus, particular combina- tions of factors included in the definitions of the metabolic syndrome confer greater risks and raise questions regarding the equal value given in the overall score to each of the components.…”
Section: Discussionmentioning
confidence: 98%
“…Together, they accounted for 67% of the variance in the measured variables. Accordingly, some cross-sectional studies propose the use of metabolic phenotypes as a screening tool for identification of adolescents who are at metabolic risk [7,22,23]. Esmaillzadeh et al [7] showed that adolescents with the Hypertriglyceride Waist (HW) phenotype had significantly higher prevalence of all metabolic risk factors except elevated fasting glucose than those without the HW phenotype.…”
Section: Discussionmentioning
confidence: 99%